Design and Analysis of Smart Grid Systems for Improved Energy Reliability - Arsyad, Andi Muhammad; Firdaus, La Ode Ahmad (RESWARA: Jurnal Riset Ilmu Teknik, 2025)
The increasing complexity of modern power systems and the growing penetration of renewable energy sources have made energy reliability a critical challenge in smart grid development. Smart grids integrate advanced information, communication, and control technologies to enhance system flexibility, efficiency, and resilience. This study aims to design and analyze smart grid systems with a specific focus on improving energy reliability through cyber-physical integration, intelligent monitoring, and advanced optimization techniques. A systematic literature-based analytical method was employed, synthesizing findings from recent journal articles and conference proceedings related to smart grid reliability, artificial intelligence, Internet of Things integration, and cyber-power interdependencies. The results indicate that the incorporation of intelligent sensing, real-time data analytics, AI-driven optimization, and robust communication architectures significantly enhances reliability indices such as SAIFI and SAIDI while reducing outage durations and cascading failure risks. Furthermore, the analysis highlights that holistic reliability modeling considering both cyber and physical layers provides more accurate and resilient system designs. This study contributes a comprehensive design-oriented perspective that integrates technological, analytical, and managerial dimensions of smart grid reliability. The findings are expected to support policymakers, system planners, and researchers in developing reliable and sustainable smart grid infrastructures.